Sialyl Lewis(x)-P-selectin cascade mediates tumor–mesothelial adhesion in ascitic fluid shear flow - Li, Shan-Shan (Nat Commun, 2019)
Organ-specific colonization suggests that specific cell–cell recognition is essential. Yet, very little is known about this particular interaction. Moreover, tumor cell lodgement requires binding under shear stress, but not static, conditions. Here, we successfully isolate the metastatic populations of cancer stem/tumor-initiating cells (M-CSCs). We show that the M-CSCs tether more and roll slower than the non-metastatic (NM)-CSCs, thus resulting in the preferential binding to the peritoneal mesothelium under ascitic fluid shear stress. Mechanistically, this interaction is mediated by P-selectin expressed by the peritoneal mesothelium. Insulin-like growth factor receptor-1 carrying an uncommon non-sulfated sialyl-Lewis(x) (sLe(x)) epitope serves as a distinct P-selectin binding determinant. Several glycosyltransferases, particularly α1,3-fucosyltransferase with rate-limiting activity for sLe(x) synthesis, are highly expressed in M-CSCs. Tumor xenografts and clinical samples corroborate the relevance of these findings. These data advance our understanding on the molecular regulation of peritoneal metastasis and support the therapeutic potential of targeting the sLe(x)-P-selectin cascade.